Vízimalmok építésével előidézett, mesterséges áradások a középkori Magyarországon - Vajda Tamás; Medievisztikai PhD-konferencia (8.) (2013) (Szeged) (2015)
Mills needed a high water level, even at the time of summer drought when most rivers could not supply them. Therefore, water supplies were gathered with dams which blocked the riverbeds. When these dams increased the water level higher than the riverbanks, mill dams caused floods with serious damages in wetter times. Several medieval diplomas refer to floods or at least to water level increases due to mills. In addition to some significant damages caused by the building of water mills, we learn about the existence of some kind of legislation in the late medieval period which protected sellers against the possible abuses of buyers in the future and at purchase they counted with potential floods caused by mill building. There are cases where floods are not mentioned, but since mills were damaged, we can suspect a water level increase. We can draw the same conclusion when the dams of the water mill were ordered to be lowered or to be moved downstream. Based on more than twenty medieval diplomas we can state that water mill builders of the 13th-15th century were able to divert streams or smaller rivers in order to exploit water power; moreover their interventions triggered local floods, or at least these increased the usual water level of the river and caused significant damages to the fields of neighbours.